Disfiguring molluscum contagiosum in a HIV-positive patient responding to antiretroviral therapy - Sen Sumit; Goswami Bidyut; Karjyi Nabendu; Bhaumik Parna (Wolters Kluwer Medknow Publications, 2009)
Molluscum contagiosum (MC) is caused by a double stranded DNA virus belonging to the pox virus family. MC lesions are usually pearly, dome shaped, small, discrete lesions with central umbilication. In HIV-positive patients atypical varieties are found. They may be large or nonumbilicated. Individual papules may join to form the agminate variety. This form is rare. Lesions of MC in healthy immunocompetent patients may occur at any part of the body including face, trunk, and limbs. Sexually active adults have lesions usually on the genitalia, pubis, and inner thigh, rarely on the face and scalp. We present a case of agminate MC occurring in a patient with acquired immunodeficiency disease responding to highly active antiretroviral therapy.